Sosok Soeharto Di Mata Masyarakat Gorontalo - Sutrisno Mohamad; Asmun Wantu; Andris K. Malae (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this research is to describe how Soeharto is in the eyes of the people of Gorontalo. The results of the research show that the figure of Suharto played an important role during the New Order era which slightly changed conditions in Indonesia which also had an impact on Gorontalo. It can be said that Soeharto himself during the New Order era was known as an extraordinary and kind person, but apart from that, there are many stories that tell about his badness where Suharto was a pretty tough person, as well as news about the case. Corruption committed by him and his son during his tenure as president during the New Order era. Suharto's role in Gorontalo was to create an army training command, which was located on Jalan Nani Wartabone, namely the first 317 Company in Gorontalo. Keywords: Soeharto, Gorontalo people, history